Critical physicochemical attributes of chitosan nanoparticles admixed lactose-PEG 3000 microparticles in pulmonary inhalation - Nasser Alhajj; Zabliza Zakaria; Idanawati Naharudin; Fakhrul Ahsan; Wenji Li; Tin Wui Wong (Elsevier, 2020)
Chitosan nanoparticles are exhalation prone and agglomerative to pulmonary inhalation. Blending nanoparticles with lactose microparticles (∼5 µm) could mutually reduce their agglomeration through surface adsorption phenomenon. The chitosan nanoparticles of varying size, size distribution, zeta potential, crystallinity, shape and surface roughness were prepared by spray drying technique as a function of chitosan, surfactant and processing conditions. Lactose-polyethylene glycol 3000 (PEG3000) microparticles were similarly prepared. The chitosan nanoparticles, physically blended with fine lactose-PEG3000 microparticles, exhibited a comparable inhalation performance with the commercial dry powder inhaler products (fine particle fraction between 20% and 30%). Cascade impactor analysis indicated that the aerosolization and inhalation performance of chitosan nanoparticles was promoted by their higher zeta potential and circularity, and larger size attributes of which led to reduced inter-nanoparticulate aggregation and favored nanoparticles interacting with lactose-PEG3000 micropaticles that aided their delivery into deep and peripheral lungs.